Another look at depressive symptoms and antiretroviral therapy adherence: The role of treatment self-efficacy. (October 2016) - Houston, Eric; Mikrut, Cassandra; Guy, Arryn; Fominaya, Adam W; Tatum, Alexander K; Kim, Jeong H; Brown, Annette
Depression has been strongly associated with poor HIV treatment adherence, but little research has explored how individuals manage to follow their regimens despite symptoms of major depression. Using a sample of antiretroviral therapy patients with clinically significant depressive symptoms ( n  = 84), we examined whether patients with optimal adherence differed from those with suboptimal adherence in terms of the types of depressive symptoms experienced and treatment self-efficacy. There were no significant differences between participants with regard to types of depressive symptoms. Findings indicate that patients with high treatment self-efficacy were more likely to report optimal levels of adherence than patients with low self-efficacy.